Usefulness of Ki-67, Mitoses, and Tumor Size for Predicting Metastasis in Carcinoid Tumors of the Lung: A Study of 48 Cases at a Tertiary Care Centre in Canada. (6th December 2015) - Joseph, M. G.; Shibani, A.; Panjwani, N.; Arab, A.; Shepherd, J.; Stitt, L. W.; Inculet, R.
Abstract : Background . Evaluation of Ki-67 index in lung carcinoid tumors (LCTs) has been of interest in order to identify high risk subsets. Our objectives are (1) to evaluate the usefulness of Ki-67 index, mitoses, and tumor size in predicting metastasis and (2) to compare the Manual Conventional Method (MCM) and the Computer Assisted Image Analysis Method (CIAM) for Ki-67 calculation. Methods . We studied 48 patients with LCTs from two academic centres in Canada. For Ki-67 calculation, digital images of 5000 cells were counted using an image processing software and 2000 cells by MCM. Mitoses/10 HPF was counted. Results . We had 37 typical carcinoids (TCs) and 11 atypical carcinoids (ACs). 7/48 patients developed metastasis. There was a positive relationship between metastasis and carcinoid type (P = 0.039 ) and metastasis and mitoses (≥2) (P = 0.017 ). Although not statistically significant, the mean Ki-67 index for ACs was higher than for TCs (0.95% versus 0.72%, CIAM, P = 0.299 ). Similarly, although not statistically significant, the mean Ki-67 index for metastatic group (MG) was higher than for nonmetastatic group (NMG) (1.01% versus 0.71% by CIAM, P = 0.281 ). However when Ki-67 index data was categorized at various levels, there is suggestion of a useful cutoff (≥0.50%) to predict metastasis (P = 0.106, CIAM). A significantly higher proportion of patients with mitosis ≥2 and Ki-67 index ≥0.50% had metastasis (P = 0.033 ) compared to other patients. Similarly patients with tumor size ≥3 cm and Ki-67 ≥0.50% had a greater percentage of metastases than others (P = 0.039 ). Although there was a strong correlation between two (MCM versus CIAM) counting methods (r = 0.929, P = 0.001 ), overall the calculated Ki-67 index was slightly higher by MCM (range 0 to 6.4, mean 1.5) compared to CIAM (range 0 to 2.9, mean 0.75). Conclusion . This study confirms that mitoses ≥2 is a powerful predictor of metastasis in LCTs. Although this is a small sample size, there is suggestion that analysis of Ki-67 index along with mitoses and tumor size may be a useful adjunct for predicting metastasis in LCTs.